The effects of additives on Tapuy (rice wine) quality - Quines, Laurence Marvin E.
ABSTRACT The effects of additives namely duhat (Syzigium cumini Skeels) bark, tangal (Vateria indicans) bark, and guava leaves (Psidium guava Linn) on PhilRice Tapuy were determined during storage. Tapuy samples including control (RW), tapuy with duhat additives (RWD), tapuy with duhat-tangal additives (RWDT) and tapuy with duhat-tangal-guava leaves additives (RWDTG) were tested. Varying amounts of additives were used and changes in pH, titrable acidity (TA), total soluble solids (TSS), alcohol content and color of the tapuy samples were monitored during 3 months of aging. Moreover, sensory tests using Descriptive Analysis (DA) and Consumer Acceptance (CA) after aging were conducted. Results showed that pH of the samples with additives significantly differed (p<0.05) after 3 months of aging. It was observed that pH of the treated samples weakly increased (r^2 = 0.0027 to 0.0304) through time. However, TA and TSS values of the control sample and the treated samples were not significantly different (p>0.05). It was also found out that TA (r^2= 0.03 to 0.5493) weakly decreased through storage time. Results showed that alcohol content and color were significantly different (p<0.05) across the samples and weakly increased (r^2 = 0.246 to 0.785); (r^2 = 0.0071 to 0.3937) during 3 months of aging, respectively. Furthermore, sensory test showed that the untreated (control)sample was significantly different (p<0.05) in terms of color and clarity. In addition, the use of additives to tapuy did not sustain or improve the quality of tapuy but contributed negatively to its color and clarity acceptance. Results also showed that untreated and treated tapuy samples were comparable for the other sensory attributes. Additionally, correlation analysis showed that sweetness (r = 0.972) and dryness (r = 0.906) significantly contributed (p<0.05) to the overall acceptance of tapuy.